A study on factors contributing to impulsive buying behaviour among consumers in social commerce - Sze, Boon Chin (2022)
With the rising of online shopping and the emergence of social commerce, consumers’ buying behaviour changed from rational buying to impulsive buying. This research aims to identify the factors that contribute to impulsive buying behaviours among consumers in social commerce. Hence, the Stimulus-OrganismResponse Model (SOR) was applied to investigate consumer emotion in response to stimuli and the subsequent positive or negative behaviours. Using the SOR model as a reference, scarcity, serendipitous information, and electronic word of mouth will be the stimulus, the urge to buy impulsively will be the organism, and impulsive buying behaviour will be the response. Four hypotheses were developed to identify the relationship between the variables. Questionnaires were prepared using Google Form and distributed to 250 respondents who had purchased a product from social media sites. The data collected from respondents were decoded and analysed by using SmartPLS software. Not only that, theoretical and managerial implications were proposed with the hope that future researchers and practitioners can serve as a reference for the experimental method to further understand consumer’s buying behaviour in social commerce.